GAMBARAN TINGKAT NEUROPATI PERIFER PADA PASIEN DIABETES MELITUS TIPE 2 DI RSUD WANGAYA - Ni Putu Ari Wahyuni; Gusti Ayu Ary Antari; Ni Luh Putu Eva Yanti (Coping: Community of Publishing in Nursing, 2021)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease caused by an increase in blood sugar levels in the blood which will lead complication. Peripheral neuropathy is one of the most common chronic complication in T2DM patients. Chronic hyperglycemia in T2DM causes damage to the peripheral nerves, namely autonomic, sensory, and motor nerves, and then triggers neuropathy. The purpose of this study was to determine the level of peripheral neuropathy in type 2 diabetes mellitus patients in Wangaya District Hospital. This research is a descriptive explorative quantitative with a cross-sectional design. As many as 73 respondents were obtained through a purposive sampling technique. Data were analyzed using univariate analysis. The majority of respondents ages ranged from 56-65 years (53,4%), most are female (56.2%), their last education was elementary school (27.4%),. and most of their occupations were in other categories, namely housewives, farmers, and laborers (58.9%). Most of the respondents have T2DM for more than 5 years (45.2%) and have GDS levels of 201-300 mg/dL (60,3%). The majority of respondents have concomitant hypertension (39.7%) and consumed OHO (67.1%). The results show as many 4,1% did not experience neuropathy, experienced mild neuropathy 61.6%, moderate neuropathy 31.5%, and severe neuropathy 2.7%. Therefore, the results of this study provide an overview of the need for strategic efforts to prevent the progression of neuropathy.